Endomyocardial Biopsy-Induced Coronary-Cameral Fistula - Trenson, Sander; Hofer, Daniel; Sokolski, Mateusz; Mikulicic, Fran; Ruschitzka, Frank; Flammer, Andreas J.; Winnik, Stephan (Cardiology and Cardiovascular Medicine, 2020)
A 45-year-old patient presented for coronary allograft vasculopathy screening 7 years after heart transplantation. Coronary angiography revealed a fistula between the left anterior descending artery and the right ventricle.